Industry 4.0 Applications in Nigeria: Evaluating the Practices via an MCDM Approach - AFOLABI, FAROUK (İstanbul Kültür Üniversitesi, 2023)
Hunger and malnutrition are major concerns in the world especially in under developed countries. The implementation of technology specifically in the agricultural economy is also a vital issue since it directly contributes to the wellbeing of people and feeding the global growing population. With an increasing number of individuals paying much attention to food security and reduction in food wastage, the supply chain in the agri-food sector has to be traceable throughout the chain for better productivity. Certainly, Agriculture 4.0 practices may provide different solutions to several problems in the sector. This thesis provides several insights on the productivity, agriculture, Industry 4.0, supply chain networks, multi criteria decision making (MCDM) methods and food security. The main purpose of the study is to select the best Industry 4.0 application to be implemented in agriculture sector in Nigeria. For this purpose, three experts are surveyed to obtain their opinions about the importance of the criteria that could be considered in the alternative selection process, and the relative importance of each alternative in accordance with each criterion. A hybrid methodology based on Analytic Hierarchy Process (AHP) and TOPSIS is implemented, and the best alternative is selected.
Nijerya'da Endüstri 4.0 Uygulamaları: Yöntemlerin Bir Çok Amaçlı Karar Verme Yaklaşımıyla Değerlendirilmesi
▪ Yüksek lisans tezi.
Keywords: Agriculture 4.0; MCDM; Industry 4.0; AHP; TOPSIS